Excavating the organ trade: an empirical study of organ trading networks in Cairo, Egypt - Columb, Seán (The British journal of criminology, 2017)
Legislative action in response to the organ trade has centred on the prohibition of organ sales and the enforcement of criminal sanctions targeting ‘trafficking’ offences. This paper argues that the existing law enforcement response is not only inadequate but harmful. The analysis is based on empirical data gathered in Cairo, Egypt, among members of the Sudanese population who have either sold or arranged for the sale of kidneys. The data suggest that prohibition has pushed the organ trade further underground increasing the role of organ brokers and reducing the bargaining position of organ sellers, leaving them exposed to greater levels of exploitation.